2018
DOI: 10.1002/jbio.201800054
|View full text |Cite
|
Sign up to set email alerts
|

Triphenylphosphonium cation: A valuable functional group for antimicrobial photodynamic therapy

Abstract: Light-mediated killing of pathogens by cationic photosensitisers is a promising antimicrobial approach that avoids the development of resistance inherent to the use of antimicrobials. In this study, we demonstrate that modification of different photosensitisers with the triphenylphosphonium cation yields derivatives with excellent photoantimicrobial activity against Gram-positive bacteria (ie, Staphylococcus aureus and Enterococcus faecalis). Thus, the triphenylphosphonium functional group should be considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 35 publications
1
29
1
Order By: Relevance
“…The perylenequinone derivative hypericin-glucamine is another example of a synthetic PS derivative that promotes periodontal repair [ 132 ]. Bresolí-Obach et al [ 133 ] reported that a phenalenone PS showed significant photostability and phototoxicity against Gram-positive bacteria. Additionally, in that study, a triphenylphosphonium derivative PS selectively killed Gram-positive bacteria.…”
Section: Synthetic Derivatives Of Natural Pssmentioning
confidence: 99%
“…The perylenequinone derivative hypericin-glucamine is another example of a synthetic PS derivative that promotes periodontal repair [ 132 ]. Bresolí-Obach et al [ 133 ] reported that a phenalenone PS showed significant photostability and phototoxicity against Gram-positive bacteria. Additionally, in that study, a triphenylphosphonium derivative PS selectively killed Gram-positive bacteria.…”
Section: Synthetic Derivatives Of Natural Pssmentioning
confidence: 99%
“…In particular, following the major concerns around MDR bacteria, several new PS have been tested, adapted or developed for aPDT [30]. In this sense, positively charged PS appear promising for aPDT as they can interact electrostatically with the negatively charged bacterial membrane, and the synthesis of several PS functionalised with small cationic functional groups has been reported [31][32][33][34][35]. Nonetheless, two main concerns can arise from this strategy: (i) a poor target selectivity since such cationic species, due to electrostatic interactions with mammalian cells, lead to off-target damage, and (ii) the poor efficiency of aPDT against a certain type of pathogens, in particular Gram− bacteria and biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-established that some lipophilic cations, for example of the triphenylphosphonium class 96 can enter bacterial cells in a process driven by the cytoplasmic membrane potential (negative inside) and have even been conjugated to photosensitisers to increase their antibacterial effect in the cytoplasm. 97 Multiple active transporters may also exist for many large cationic lipophilic molecules. 98 The very small degrees of dark toxicity of 1 towards S. aureus and E. coli (Fig.…”
Section: Resultsmentioning
confidence: 99%